Breast Tissue Expanders with Magnetic Ports: Clinical Experience at 1.5 T. Issue 6 (December 2016) - Thimmappa, Nanda Deepa; Prince, Martin R.; Colen, Kari L.; Ahn, Christina Y.; Dutruel, Silvina P.; Boddu, Srikanth R.; Greenspun, David T.; Vasile, Julie V.; Chen, Constance M.; Usal, Hakan; Rohde, Christine H.; Redstone, Jeremiah S.; et al.
Abstract : Background: The purpose of this study was to evaluate breast tissue expanders with magnetic ports for safety in patients undergoing abdominal/pelvic magnetic resonance angiography before autologous breast reconstruction. Methods: Magnetic resonance angiography of the abdomen and pelvis at 1.5 T was performed in 71 patients in prone position with tissue expanders with magnetic ports labeled "MR Unsafe" from July of 2012 to May of 2014. Patients were monitored during magnetic resonance angiography for tissue expander–related symptoms, and the chest wall tissue adjacent to the tissue expander was examined for injury at the time of tissue expander removal for breast reconstruction. Retrospective review of these patients' clinical records was performed. T2-weighted fast spin echo, steady-state free precession and gadolinium-enhanced spoiled gradient echo sequences were assessed for image artifacts. Results: No patient had tissue expander or magnetic port migration during the magnetic resonance examination and none reported pain during scanning. On tissue expander removal (71 patients, 112 implants), the surgeons reported no evidence of tissue damage, and there were no operative complications at those sites of breast reconstruction. Conclusion: Magnetic resonance angiography of the abdomen and pelvis in patients with certain breast tissue expanders containing magnetic ports can be performed safely at 1.5 T for pre–autologous flap breast reconstruction perforator vessel mapping. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.